The violence of peace : America's wars in the age of Obama - Carter, Stephen L., 1954- (New York : Beast Books, 2011)
Presents an analysis of Barack Obama's views on war and the military in the first two years of his presidency, discussing his evolution from being a peace candidate to being a president conducting two wars and how this change affects national security and the nation's future.
Eliminating enemies -- No equivalence -- The rights and dignities of strangers -- The American proviso.
Includes bibliographical notes and index.
Keywords: Obama, Barack -- Military leadership; National security -- United States; Afghan War, 2001- -- Political aspects -- United States; Iraq War, 2003-2011 -- Political aspects -- United States; United States -- Military policy